Diffuse high-grade gliomas with H3 K27M mutations carry a dismal prognosis independent of tumor location. Issue 1 (4th August 2017) - Karremann, Michael; Gielen, Gerrit H; Hoffmann, Marion; Wiese, Maria; Colditz, Niclas; Warmuth-Metz, Monika; Bison, Brigitte; Claviez, Alexander; van Vuurden, Dannis G; von Bueren, André O; Gessi, Marco; Kühnle, Ingrid; et al.
Abstract: Background: The novel entity of "diffuse midline glioma, H3 K27M-mutant" has been defined in the 2016 revision of the World Health Organization (WHO) classification of tumors of the central nervous system (CNS). Tumors of this entity arise in CNS midline structures of predominantly pediatric patients and are associated with an overall dismal prognosis. They are defined by K27M mutations in H3F3A or HIST1H3B/C, encoding for histone 3 variants H3.3 and H3.1, respectively, which are considered hallmark events driving gliomagenesis. Methods: Here, we characterized 85 centrally reviewed diffuse gliomas on midline locations enrolled in the nationwide pediatric German HIT-HGG registry regarding tumor site, histone 3 mutational status, WHO grade, age, sex, and extent of tumor resection. Results: We found 56 H3.3 K27M-mutant tumors (66%), 6 H3.1 K27M-mutant tumors (7%), and 23 H3-wildtype tumors (27%). H3 K27M-mutant gliomas shared an aggressive clinical course independent of their anatomic location. Multivariate regression analysis confirmed the significant impact of the H3 K27M mutation as the only independent parameter predictive of overall survival ( P = 0.009). In H3 K27M-mutant tumors, neither anatomic midline location nor histopathological grading nor extent of tumor resection had an influence on survival. Conclusion: These results substantiate the clinical significance of considering diffuse midline glioma, H3 K27M-mutant, as a distinct entity corresponding to WHO grade IV, carrying a universally fatal prognosis.